Modelling Back-to-Back Converter with Average Model in Wind Power System Using DFIG - Harumwidiah, Anisa; Ashari, Mochamad; Riawan, Dedet Candra (IPTEK Journal of Proceedings Series, 2014)
The total energy consumption in this year increase significantly. Most of energy that used come from fossil fuel. The use of fossil fuel can cause a lot of pollution and the amount of them is decreased. Therefore, many countries developing renewable energy system. One of renewable energy system is wind power using Doubly Fed Induction Generator (DFIG). DFIG supplies AC current from the stator winding that are connected directly to the grid and rotor winding DFIG are also connected to the grid through power electronic converter. The type of this converter is back-to-back converter. In general, this converter used switching model. However, this model produce a slow simulation and high riplle. To solve this problem DFIG with average model in back-to-back converter is studied in this research. This design operated by controlling the rotor speed DFIG to produce maximum power and preserve the value of DC link voltage remains constant.